The validity of routine individuated programmatic data in HIV surveillance assessed over a 10-year period. - Nisha Jacob; Brian Rice; Andrew Boulle (International Journal of Population Data Science, 2022)
Objectives In the Western Cape, South Africa, public-sector individual-level routine data are consolidated from multiple non-EMR sources through the Provincial Health Data Centre (PHDC).  This enables the description of temporal changes in population-wide antenatal HIV sero-prevalence. We evaluated the validity of these data compared to aggregated program data and sentinel surveys.